Cooking Skills Index: Development and reliability assessment - MARTINS, Carla Adriano; Galastri BARALDI, Larissa; Baeza SCAGLIUSI, Fernanda; Slater VILLAR, Betzabeth; MONTEIRO, Carlos Augusto (Revista de Nutrição, 2023)
Objective Describe the development and the reliability assessment of an index that evaluates the confi dence in performing cooking skills considered relevant in Brazil. Methods The development of the Cooking Skills Index was based on the self-effi cacy beliefs and its theoretical reference was the Dietary Guidelines for the Brazilian Population. It measures, from zero to 100, the degree of confi dence in performing ten cooking skills considered as facilitators for the implementation of Brazilian Dietary Guidelines recommendations. Experts (face validity) evaluated the index. A pilot study (n=10) and a test-retest (n=51) was conducted by telephone interviews and computerized assistance with adults responsible for food preparationat home in São Paulo. Reliability was assessed by Cronbach’s alpha, quadratic weighted kappa and prevalence and bias adjusted kappa. Results The Cooking Skills Index was coherent with the adopted theoretical framework according to the experts. It was fast and easy to apply to the participants. It showed a good internal consistency (Cronbach’s alpha >0.70) and an acceptable to excellent reproducibility (weighted kappa=0.55, adjusted kappa=0.89). Conclusion The Cooking Skills Index has a good reliability and is therefore recommended to evaluate cooking skills confidence in Brazilian studies developed in contexts similar to those of this study.